Plant-Derived Phenolic Acids Limit the Pathogenesis of Salmonella Typhimurium and Protect Intestinal Epithelial Cells during Their Interactions - Zabdiel Alvarado-Martinez; Zajeba Tabashsum; Arpita Aditya; Katherine Hshieh; Grace Suh; Matthew Wall; Aaron Scriba; George Sellers; Christa Canagarajah; Sarika Kapadia; Debabrata Biswas (Molecules, 2024)
The incidence of gastrointestinal illness attributable to Salmonella enterica serovar Typhimurium (ST) remains a concern for public health worldwide, as it can progress into systemic infections mediated by the type-three secretion system (T3SS), which allows for adherence and invasion to intestinal epithelial cells. The current study evaluates the ability of gallic acid (GA), protocatechuic acid (PA), and vanillic acid (VA) to impair the adhesion and invasion abilities of ST to a human epithelial (INT-407) cell monolayer while also assessing their cytotoxicity. GA, PA, and VA inhibited detectable ST growth at specific concentrations but showed cytotoxicity against INT-407 cells (>20% reduction in viability) after 3 h of treatments. Adjusting the pH of the solutions had a neutralizing effect on cytotoxicity, though it did reduce their antimicrobial potency. Adhesion of ST was reduced significantly when the cells were treated with 4.0 mg/mL of VA, whereas invasion was reduced in all treatments, with GA requiring the lowest concentration (0.5 mg/mL). Relative gene expression of virulence genes after treatment with GA showed downregulation in the T3SS regulator and effector hilA and sipA, respectively. These findings suggest further use of phenolic acids in reducing the activity of key virulence factors critical during ST infection.